Visual Art and Fashion as Part of an English Department’s Afrofuturism Syllabus - Anatol, Giselle (Radical Teacher, 2022)
Images in film, paintings, sketches, and sculpture sometimes drive ideas home in ways that words on the page do not, prompting more visceral reactions and the desire to enact change instead of thinking about subjects on a more abstract level. This essay explores how the visual arts were used in a Fall 2020 course on Afrofuturist literature to supplement conventional readings, class discussions, and writing assignments, helping students to grasp many of the central principles of genre, such as re-visioning reality and undermining the “logics” established by colonial regimes, neo-colonial powers, and systemic racism; the ways that the past permeates the present; the possibilities of Africanist existence in a rich and productive future; how intersections of race, gender, and class influence artists' reconfigurations of artistic forms long dominated by White men. Several creative research projects, produced by students at the end of the semester, are described at length and analyzed to illustrate how they proccessed course concepts, and how Afrofuturist texts resonated in powerful ways during the COVID-19 pandemic.